(untitled) (Archive of Conferences, 2021)
Increasing the professionalism and competence was recognized as the main driving force of progress and activities leading to the goals of sustainable development. The modern education system involves the further improvement of the mechanisms for raising the competence of future specialists on the basis of a creative approach and an innovative system for putting them into practice. In order to increase the quality of current education system teachers should be armed with innovative methods and master the technical skills. The article looks into the requirements for the competent teaching staff